Understanding the Aspirations of Farming Communities in Developing Countries: A Systematic Review of the Literature - Nandi, R.; Nedumaran, S. (Springer, 2021)
This study surveys the panorama of research on the importance of aspirations of farming communities, identifies research gaps and prospects for future research. The analysis of 22 studies identified from 419 research articles sheds light on the relationships between aspirations, agriculture, women’s empowerment, poverty, and rural youth. Aspirations of the rural poor play a significant role in shaping their activities and investments. Furthermore, the poor and those who are exposed to natural disasters are more likely suffering from aspiration failure and their resilience needs to be built. Specifically, women’s empowerment could be supported through raising aspirations. In addition, intergenerational aspirations and corresponding investment plans in agriculture are in absolute contrast and parental desires and their children’s aspirations do not align. Overall, development program-specific research is needed to determine policies and programs that successfully and cost-effectively raise the rural poor's aspirations and thereby improve livelihoods in developing countries.